Research on the development and testing methods of physical education and agility training equipment in universities - Tan, Baohua; Tian, Shihao; Wang, Enpu; Xiao, Lu; Cao, Kan; Zheng, Beitian; Luo, Lina (Frontiers in Psychology, 2023)
Because of the problems of insufficient funds and traditional training methods in college sports agile training, an agile training system based on a wireless ad hoc network was developed to evaluate the effect of improving the sensitive quality of ordinary college students. Based on the ESP-MESH network, the lower computer realizes automatic networking between devices and tests the performance of the mesh network. Fourteen male college students received 9 weeks of agility training, with seven students in each of two groups: traditional agility training and agile equipment training. The researchers evaluated the performance of both groups in rapid disguise, body coordination, changing movements, and predictive decision-making. Results: There was no significant difference between the groups before training, but there were significant differences in the four abilities after training (P<0.01). The experimental group had significant differences in rapid direction change and physical coordination (P<0.05), and in changing movement and predictive decision-making ability (P<0.01). Conclusion: Both traditional training and agile equipment training improve the agility quality of college students, and the latter shows better results in certain abilities. However, limited by other physical qualities, the improvement of motor changes and predictive decision-making ability is not as obvious as the other two abilities.